Find \( f(g(x)) \) and \( g(f(x)) \) and determine whether the pair of functions \( f \) and \( g \) are inverses \( f(x)=9 x-5 \) and \( g(x)=\frac{x+9}{5} \) a. \( f(g(x))=\frac{9 x+56}{5} \) (Simplify your answer. Use integers or fractions for any numbers in the expression.) b. \( g(f(x))=\frac{9 x+4}{5} \) (Simplify your answer. Use integers or fractions for anyynumbers in the expression.) c. \( f \) and \( g \) are not inverses of each other: f and \( g \) are inverses of each other.
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To find \( f(g(x)) \), we substitute \( g(x) \) into \( f(x) \): \[ f(g(x)) = f\left(\frac{x+9}{5}\right) = 9\left(\frac{x+9}{5}\right) - 5 = \frac{9(x+9)}{5} - 5 = \frac{9x + 81}{5} - \frac{25}{5} = \frac{9x + 56}{5}. \] Now for \( g(f(x)) \): \[ g(f(x)) = g(9x - 5) = \frac{(9x - 5) + 9}{5} = \frac{9x + 4}{5}. \] This yields: a. \( f(g(x)) = \frac{9x + 56}{5} \) (You had it right!). b. \( g(f(x)) = \frac{9x + 4}{5} \). Now, for \( f \) and \( g \) to be inverses, we would need \( f(g(x)) = x \) and \( g(f(x)) = x \). Since neither expression simplifies to \( x \), the functions \( f \) and \( g \) are not inverses of each other: c. **f and \( g \) are not inverses of each other.**